2020
DOI: 10.3390/ijerph17114041
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Symptom Burden among Chronic Kidney Disease of Uncertain Etiology (CKDu) Patients in Girandurukotte, Sri Lanka

Abstract: Symptom burden and health-related quality of life (HRQOL) are important predictors of how a disease affects patients’ lives, especially for endemic health problems such as chronic kidney disease of uncertain etiology (CKDu). Our study describes symptom burden, HRQOL, and associated demographic and clinical variables in CKDu patients in the Girandurukotte area, Sri Lanka. A cross-sectional study included 120 CKDu patients attending the renal clinic in the endemic area. The instruments applied were the Kidney Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 62 publications
4
20
0
2
Order By: Relevance
“…Patients undergo a barrage of symptoms including fatigue and pain which are contributing factors for reduced QOL even at the early disease stages (Table 2). Our ndings are in accordance with previous studies on symptom burden of CKD/CKDu patients, where they demonstrated that excessive tiredness, sleep disturbance and pain in the bones or joints were reported more commonly among patients not requiring renal replacement therapy [21,22,33]. Moreover, in the study done to assess the symptom burden of patients with renal disease in the Anuradhapura district, the authors suggested that the high symptom burden of CKDu patients could be attributed to the low socio-economic conditions in the Anuradhapura district [34].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Patients undergo a barrage of symptoms including fatigue and pain which are contributing factors for reduced QOL even at the early disease stages (Table 2). Our ndings are in accordance with previous studies on symptom burden of CKD/CKDu patients, where they demonstrated that excessive tiredness, sleep disturbance and pain in the bones or joints were reported more commonly among patients not requiring renal replacement therapy [21,22,33]. Moreover, in the study done to assess the symptom burden of patients with renal disease in the Anuradhapura district, the authors suggested that the high symptom burden of CKDu patients could be attributed to the low socio-economic conditions in the Anuradhapura district [34].…”
Section: Discussionsupporting
confidence: 93%
“…A clear decrement in the KDQOL TM -36 sub scales is evident in the present study, implying reduced QOL across all stages of CKDu (Table 2), and the ndings are consistent with previous studies conducted with CKD/CKDu patients [9,13,[18][19][20][21][22]. Interestingly, "MCS" scores were found to be much lower compared to "PCS" scores in the early stage of the disease (group A).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations